Developmental aspects of fear: Comparing the acquisition and generalization of conditioned fear in children and adults. Issue 4 (22nd January 2016) - Schiele, Miriam A.; Reinhard, Julia; Reif, Andreas; Domschke, Katharina; Romanos, Marcel; Deckert, Jürgen; Pauli, Paul
ABSTRACT: Most research on human fear conditioning and its generalization has focused on adults whereas only little is known about these processes in children. Direct comparisons between child and adult populations are needed to determine developmental risk markers of fear and anxiety. We compared 267 children and 285 adults in a differential fear conditioning paradigm and generalization test. Skin conductance responses (SCR) and ratings of valence and arousal were obtained to indicate fear learning. Both groups displayed robust and similar differential conditioning on subjective and physiological levels. However, children showed heightened fear generalization compared to adults as indexed by higher arousal ratings and SCR to the generalization stimuli. Results indicate overgeneralization of conditioned fear as a developmental correlate of fear learning. The developmental change from a shallow to a steeper generalization gradient is likely related to the maturation of brain structures that modulate efficient discrimination between danger and (ambiguous) safety cues. © 2016 The Authors. Developmental Psychobiology Published by Wiley Periodicals, Inc. Dev Psychobiol 58: 471–481, 2016.